DEVELOPING A PRIVATE ECONOMY IN VIET NAM IN INTERNATIONAL INTEGRATION PROCESS HINDRANCES AND SOLUTIONS - Nguyen Minh Tri (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In the period of International Integration, Private Economy plays a greatly crucial role in economy, contributing to promote economy developmentally and ensure social security sustainably. Party and Government/ State of Viet Nam has loads of advocacies, policies to encourage the development of this economic composition and assert its development becoming a momentous key motivation for oriented socialist market economy. However, the development of this Private Economy in the integration process encountering some hindrances which enquires about having to possess the appropriate solutions in order to Private Economy expanding without delay, stably, and becoming keyessential driving force of economy.